Associação entre baixo peso ao nascer e defeitos do desenvolvimento do esmalte : revisão sistemática e metanálise - Dantas, Eugênia Lívia de Andrade (2024)
Introduction: Developmental enamel defects (DED) are alterations that can be present in deciduous and permanent teeth and have been associated with factors related to the perinatal period, such as birth weight. Objective: To carry out a systematic review with meta-analysis to assess whether low birth weight (including very low birth weight) is associated with DED in deciduous and permanent teeth. Methodology: The eligibility criteria were outlined following the PECO framework, with the population (P) being children and adolescents, the exposure (E) group with low birth weight, the control (C) with normal birth weight evaluating enamel development defects as the outcome (O). The study protocol was registered with PROSPERO (CRD42017078004), following PRISMA recommendations. The bibliographic search was carried out in the following databases: MEDLINE (via PubMed), ISI Web of Science, LILACS, SCOPUS and Cochrane Library until November 2023. After searching the databases, duplicates were removed from all retrieved records using the online application Rayyan®. The selection of articles, data collection and assessment of methodological quality were carried out independently by two reviewers. Methodological quality was assessed according to the guideline described by Fowkes and Fulton and the risk of bias was assessed using the Risk of Bias in Non-Randomized Studies of Exposures (ROBINS-E) tool. Twenty-two meta-analyses (α = 0.05) were carried out to assess the association between DED/Incisor Molar Hypomineralization (MIH) and birth weight, according to the type of dentition (deciduous or permanent), analyzed by subgroups according to the risk of bias (high or very high). The certainty of the evidence was assessed using the GRADE tool. Results: 1.622 publications were found after an electronic search, of which 55 were included for qualitative analysis, of which 47 articles were included in the quantitative analysis. The meta-analysis detected an association between very low birth weight (VLBW) and DED in deciduous teeth (RR: 2.82; 95% CI: 2.27 - 3.51, p<0.0001; power>99.9%) and (Cohen's H: 0.48; 95% CI: 0.38 - 0. 58, p<0.0001; power>99.9%) and low birth weight (LBW) and DED in deciduous teeth RR=1.56 (95% CI: 1.22 - 2.00, p=0.0004; power=94.1%) and Cohen's H= 0.20 (95% CI: 0.10 - 0.31, p=0.0002; power=96.2%). Neonates with low birth weight were approximately 1.25 (95% CI: 1.02-1.35) times more likely to have MIH. Low birth weight and very low birth weight were associated with enamel hypoplasia in both effect sizes. A low and very low quality of certainty evidence was obtained through GRADE analysis. Conclusion: The association found between LBW and DED/MIH is at high risk of bias.